Exploring the Potential of Nanotechnology in Pediatric Healthcare: Advances, Challenges, and Future Directions - Hossein Omidian; Kwadwo Mfoafo (MDPI AG, 2023)
The utilization of nanotechnology has brought about notable advancements in the field of pediatric medicine, providing novel approaches for drug delivery, disease diagnosis, and tissue engineering. Nanotechnology involves the manipulation of materials at the nanoscale, resulting in improved drug effectiveness and decreased toxicity. Numerous nanosystems, including nanoparticles, nanocapsules, and nanotubes, have been explored for their therapeutic potential in addressing pediatric diseases such as HIV, leukemia, and neuroblastoma. Nanotechnology has also shown promise in enhancing disease diagnosis accuracy, drug availability, and overcoming the blood-brain barrier obstacle in treating medulloblastoma. It is important to acknowledge that while nanotechnology offers significant opportunities, there are inherent risks and limitations associated with the use of nanoparticles. This review provides a comprehensive summary of the existing literature on nanotechnology in pediatric medicine, highlighting its potential to revolutionize pediatric healthcare while also recognizing the challenges and limitations that need to be addressed.